PEMANFAATAN TEPUNG LABU KUNING MODIFIKASI HYDROGEN RICH WATER KEPADA MASYARAKAT - Gita Indah Budiarti; Ayu Wulandari; Siti Mutmaina (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2020)
Pumpkin flour is one alternative wheat substitute flour that has an advantage in terms of nutritional value, other than that the pumpkin fruit in Indonesia is quite abundant so it is potential to be used as food as well as subtituen wheat flour. The purpose of this research is to know the effect of treatment by soaking the pumpkin using hydrogen rich water to the physicochemical characteristics of starch as well as the texture, aroma and taste of processed pumpkin flour cake. The method done is to immersion using hydrogen rich water pH 5 and 9 for 1, 2, 3, 4 and 5 hours and then dried using a microwave and mashed with a blender then sifted using screening. Analysis conductedÂ  favorite test. The results showed that in the processed cakes shows the texture, aroma and distinctive flavor of the yellow pumpkin. Pumpkin flour is good to be used as a mixture of wheat flour in the manufacturing of various food processed such as wet cakes and biscuits.